APPLICATION OF SUGENO FUZZY INFERENCE ALGORITHM IN THE PROBLEM OF PREDICTING THE RESIDUAL LIFE OF AVIATION RADIOTECHNICAL EQUIPMENT - Trần Minh Hải; Ku Thanh Phong; Nguyen The Thang; Nguyễn Thanh Sáng; N.K. Yurkov; Phạm Văn Tú (Надежность и качество сложных систем)
Background. The problem of increasing noise immunity, secrecy, reliability, throughput and range of ground and airborne electronic systems (RES), as well as determining the values of the residual resource, is relevant in the modern world. The technical condition of radio engineering systems depends on many factors, the main ones of which will be taken into account. Knowing the standard values of the diagnostic parameters of units and assemblies, it is possible to predict the residual resource of the system, i.e. its operation from the moment of technical diagnostics of the parameter until the moment it receives the limit value. Materials and methods. The paper considers the application of the Sugeno-Kan fuzzy-logical inference algorithm for assessing the residual resource for aviation radio engineering equipment. Results. The paper presents a theoretical representation of fuzzy logic, residual resource and the application of fuzzy-logical inference algorithms for solving the problems of extending and predicting the residual resource of aviation radio engineering devices. Conclusions. Technical recommendations for practical applications of extending and predicting the residual resource of technical products are obtained.